2003
DOI: 10.1162/105474603322391631
|View full text |Cite
|
Sign up to set email alerts
|

Real Handball Goalkeeper vs. Virtual Handball Thrower

Abstract: R eal Hand b all Go alk eep er v s. Virt u al Hand b all Throw er A b st r a ctVirtual reality offers new tools for human motion understanding. Several applications have been widely used in teleoperation, military training, driving and ying simulators, and so forth. We propose to test if virtual reality is a valid training tool for the game of handball. We focused on the duel between a handball goalkeeper and a thrower. To this end, we de ned a pilot experiment divided into two steps: an experiment with real s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 16 publications
1
50
0
Order By: Relevance
“…The CG animations offer, at least partly, the possibility that they can be used for evaluating perceptual skills in tennis. Bideau et al (2003;2004) examined handball goalkeepers' responses when faced with an opponent's throw in a VR environment as compared to a real situation. The study demonstrated that the VR situation was realistic enough that it made it possible for researchers to evaluate the goalkeeper's natural reactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CG animations offer, at least partly, the possibility that they can be used for evaluating perceptual skills in tennis. Bideau et al (2003;2004) examined handball goalkeepers' responses when faced with an opponent's throw in a VR environment as compared to a real situation. The study demonstrated that the VR situation was realistic enough that it made it possible for researchers to evaluate the goalkeeper's natural reactions.…”
Section: Discussionmentioning
confidence: 99%
“…While the point-light displays are a potentially valuable tool to permit the manipulation of display kinematics, the computeranimated characters also have significant potential for the simulated presentation of sport situations because they allow exact changes to be made in various parameters, such as the movement, body, characteristics, contour, texture, and perspective of the image. In recent times, with the development of computer graphics (CG) technology, several sports science studies have begun to use humanlike CG animations as a visual stimulus that plays handball (Bideau et al, 2003;2004), runs (Hodgins et al, 1998), and plays tennis (Fukuhara et al, 2005;Pollick et al, 2001). The advantage of using CG animations is that they can precisely control kinematic features and also provide information about appearance (e.g., contour, texture, and size).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such experimental paradigm has been used in many studies (Bideau, 2003 ;Zaal, 2003 ;Richard, 1994). However, a few of these involve haptic feedback (Richard, 1998 ;Jeong, 2004).…”
Section: Virtual Catch Ballmentioning
confidence: 99%
“…Both skin conductance, heart rate and heart rate variability have been shown to respond significantly in the context of general social situations [16], and social situations that are highly stressful [17]. It has also been found that there are similarities in behavior when participants play handball in virtual reality compared to physical reality [18]. In some of these examples anxiety, as measured through physiological responses, is one sign that people are responding to the virtual events as if they were really happening.…”
Section: Introductionmentioning
confidence: 99%